2019
DOI: 10.1177/0954406219838579
|View full text |Cite
|
Sign up to set email alerts
|

A damage identification method for a thin plate structure based on PVDF sensors and strain mode

Abstract: Damage identification methods for engineering structures based on vibration parameters have the advantages of easy detection and high precision; however, structural strain information is more sensitive to structural damage than displacement information. Traditional resistance strain sensors have low accuracy and poor stability when measuring structural strains. Therefore, this paper uses a highly sensitive polyvinylidene fluoride dynamic strain sensor to identify structural damage in a thin plate. The polyviny… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 26 publications
0
6
0
Order By: Relevance
“…The structural displacement vibration response equation for a multi-degree-of-freedom vibration system can be expressed as follows, using the theory of mode superposition [45,46]:…”
Section: The Strain Mode Vibration Pattern's Derivationmentioning
confidence: 99%
“…The structural displacement vibration response equation for a multi-degree-of-freedom vibration system can be expressed as follows, using the theory of mode superposition [45,46]:…”
Section: The Strain Mode Vibration Pattern's Derivationmentioning
confidence: 99%
“…ω i , and ζ i are the ith-order natural frequency and damping ratio, respectively. It is worth mentioning that the strain response is more sensitive to local damage than the displacement response [29][30][31][32] because the strain mode shape is a second-order differentiation of the displacement mode shape, while the differentiation operation further amplifies the abrupt changes in the curve caused by damage. Consequently, the strain response data are selected for the damage identification study.…”
Section: Second-order Strain Statistical Moments (Sssm)mentioning
confidence: 99%
“…Anastasopoulos et al [16] performed modal analysis by improving the fiber optic strain sensing technique and identified structural damage by using strain mode shapes and strain ratio. Cui et al [17] suggested a novel damage identification index for thin plates based on the LU decomposition of the strain flexibility matrix. However, it was noted that the measurement of the point-strain sensor is too local for SHM as these point strain sensors only collect structural local information and are unable to adequately capture structural damage information unless they are installed close enough to the damage areas [18,19].…”
Section: Introductionmentioning
confidence: 99%